Semiotics of Tobacco: the Case of Runeberg’s Pipe - Hallila, Mika (Journal of Applied Cultural Studies, 2015)
The essay introduces an approach called the semiotics of tobacco by analyzing one narrative poem. The analyzed poem is Fänrik Stål (1848) by Johan Ludvig Runeberg, the national poet of Finland. Fänrik Stål is traditionally considered nationalistic and patriotic. When analyzed in the context of semiotic of tobacco, the traditional way to interpret it is challenged. In the end, this case analysis of Finnish literature is used as an example of broader problems in representing tobacco in literature in order to establish the approach of the semiotics of tobacco.